Bean yield and yield componentes as affected by fertilizer and plant population - Edje, O.T.; Mughogho, L.K.; Ayonoadu, U.W.U (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Two determinate cultivars of bean (Phaseolus vulgaris L.) were grown at three fertilizer levels (0, 400, and 800 kg/ha) and with three populations (111,000, 222,000, and 444,000 plants/ha) in row ridges spaced apart at 45 cm spacing. The grain yields, across cultivars and populations, for the low, medium, and high fertilizer levels were 1216, 1514, and 1670 kg/ha, respectively. Overall, yield (g/plant), seed size, branches per plant, and pod length also increased with fertilizer level.